Kemudahsampaian mempengaruhi nilai harta tanah di Bukit Gambir - Salleh, Nurulliza (2014)
Highway accessibility is one of the facilities that will affect the value of the property and the development of a region. Government awareness of the importance of the highway as a link between one city to another city, especially big cities like Kuala Lumpur, Johor Bahru, Penang and other cities have resulted in rapidly growing highways built. Not only that, but the accessibility is also able to save time and ease of travel from one destination to another. Therefore, the main objective of this study was to investigate the effect of increasing the accessibility of the property and identify the perceptions of local residents against the construction of the interchange at Bukit Gambir. To achieve the main objective, the data obtained from the Department of Valuation and Property Services Muar. The data were analyzed using SPSS application software and showed that the soil was increased when the construction of this interchange was built. The second objective is achieved by analyzing the information obtained from the distribution of questionnaires to the respondents. The second objective, found 56 percent of voters say the construction of the interchange is affecting development around Bukit Gambir. In short, accessibility is very important as a link between one destination to another and affect the increase in the value of a property. From the findings that have been obtained, given appropriate recommendations to the relevant authorities and further research are also proposed.